Strattis, tragedy, and comedy - Miles, Sarah N. (2009)
This study comprises a translation, textual commentary, and discussion of the fragments of the Old comic dramatist Strattis which engage with tragedy. It forms the centre of a wider examination of the art of paratragedy and tragic parody in Old Comedy because paratragedy represents the earliest reception of tragedy and one that is contemporary with the initial live performances of tragic plays. Ancient and modern scholarship alike has viewed Aristophanes as the dominant figure in the art of paratragedy and tragic parody. Strattis, a contemporary of Aristophanes, was active in the late fifth and early fourth centuries BC and the fragments of his comedies indicate a sustained and wide ranging interaction with contemporary tragedy which is rivalled only by Aristophanic comedy. This is particularly remarkable since the extant corpus of Strattis numbers less than ninety fragments.